Brief of the physical properties of SiC for accident tolerant fuel cladding material; Научная инициатива иностранных студентов и аспирантов; Т. 2 - Aljasar Shojaa Ayed Ali (Science as a vocation and career, 2021)
Заглавие с титульного экрана